Determination of bisphenol A, bisphenol F and bisphenol S in plant-based food by compound immunoaffinity column coupled with high performance liquid chromatography Tandem Mass Spectrometry - HAN Muke; YIN Jie; ZHANG Jing; SHAO Bing (Zhongguo shipin weisheng zazhi, 2021)
ObjectiveTo develop an analytical method for determination bisphenol A, bisphenol F and bisphenol S in fruit (apple), vegetable (spinach), cereal (rice flour) and infant cereal supplement (infant formula rice flour) by compound immunoaffinity column coupled with high performance liquid chromatography Tandem Mass Spectrometry.MethodsThe samples were extracted with acetonitrile or 80% methanol solution, purified by a compound immunoaffinity column, separated by ACQUITY UPLC BEH C18 column, and detected by HPLC-MS/MS.ResultsThe linearity of the three bisphenol compounds in the corresponding concentration range was good with relative coefficient of R2 greater than 0.999. The recoveries of the three kinds of bisphenol were in the range of 94.81%-111.12%, the relative standard deviations were in the range of 1.25%-11.50%, and the matrix effect was in the range of -10.23%-5.46% at low, medium and high spiked concentrations. The limits of detection were 0.015-0.15 μg/kg and the limits of quantification were 0.05-0.5 μg/kg.ConclusionThis method is based on antigen and antibody specific binding immunoaffinity column to purify the samples, with good reproducibility and high sensitivity, and can effectively separate and detect bisphenol substances in apple, spinach, rice flour and infant formula rice flour. It could be applied to the qualitative and quantitative detection of bisphenol substances in these four kinds of food.